Using Static Culture Method to Increase the Production of Acetobacter Xylinum Bacterial Cellulose - Jialing Chen; Fan Hong; Huanda Zheng; Laijiu Zheng; Bing Du (Journal of Natural Fibers)
Bacterial cellulose is a natural polymer, usually produced through synthetic (chemically defined) or natural media. However, the current methods of bacterial cellulose production are not ideal because of their low productivity and large number of byproducts. In order to improve the yield of bacterial cellulose, the influence of medium composition, culture time, culture temperature and culture pH on the production of bacterial cellulose by Acetobacter xylinum ATCC 23,767 was studied by single factor method. The optimal medium composition for Acetobacter xylinum can be analyzed by Thermal field emission scanning electron microscopy (TF-SEM) as glucose (20 g/L), yeast extract (5 g/L), peptone (5 g/L), citric acid (2 g/L). Using the logarithmic calculation method, we can determine that the optimal culture conditions are controlled by initial pH of the culture medium of 6 and constant static culture at 28°C for 9 days. Using TF-SEM, Fourier transform infrared (FT-IR) spectroscopy and water contact angle test, the best post-treatment solution can be selected as sodium hydroxide (1%). The results showed that the yield of bacterial cellulose could reach up to 8.5 g/L under the above conditions, and the obtained product exhibited a dense three-dimensional network structure.